WAYS TO IMPROVE THE RESULTS OF DIAGNOSIS AND TREATMENT OF SEVERE FORMS OF PURULENT-INFLAMMATORY DISEASES OF SOFT TISSUES COMPLICATED BY SEPSIS - Kayumova, D.T.; Korikhonov, D.N.; Shukurov, F.I.; Khaydarov, F.N.; Gulmanov, I.D.; Marupov, I.A.; Kurbanov, O.M.; Sattarov, O.T.; Azizova, P.Kh.; Ruzmatov, P.Yu.; Sharipov, Yu.Yu. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The most severe and rapidly progressing tissue infections, accompanied by severe intoxication and sepsis, are necrotising infections. Material and methods. 108 patients with necrotizing soft tissue infections were examined and treated. Among them, fasciitis (83 patients), cellulitis (11 patients) and myositis (14 patients) were distinguished. Clinical, laboratory, in-depth microbiological and histological studies were used. Results. Necrotizing soft tissue infections are characterized by microbial polymorphism without a clear correlation between the clinical course and the microbiological landscape. The impossibility of excluding the diagnosis of necrotizing soft tissue infection on the basis of the clinical picture is an indication for surgical revision of all layers of soft tissues.